Quadratic relationship between systolic blood pressure and white matter lesions in individuals with hypertension. Issue 1 (4th January 2023) - Woldstad, Christopher; Rusinek, Henry; Sweeney, Elizabeth; Butler, Tracy; Li, Yi; Tanzi, Emily; Mardy, Christopher; Harvey, Patrick; de Leon, Mony J.; Glodzik, Lidia
Abstract : Background: There is a well documented relationship between cardiovascular risk factors and the development of brain injury, which can lead to cognitive dysfunction. Hypertension (HTN) is a condition increasing the risk of silent and symptomatic ischemic brain lesions. Although benefits of hypertension treatment are indisputable, the target blood pressure value where the possibility of tissue damage is most reduced remains under debate. Method: Our group performed a cross-sectional ( n = 376) and longitudinal ( n = 188) study of individuals without dementia or stroke (60% women n = 228, age 68.5 ± 7.4 years; men n = 148, age 70.7 ± 6.9 years). Participants were split into hypertensive ( n = 169) and normotensive ( n = 207) groups. MR images were obtained on a 3T system. Linear modeling was performed in hypertensive and normotensive cohorts to investigate the relationship between systolic (SBP) and diastolic (DBP) blood pressure, white matter lesion (WML), and brain volumes. Results: Participants in the hypertensive cohort showed a quadratic relationship between SBP and WML, with the lowest amounts of WML being measured in participants with readings at approximately 124 mmHg. Additionally, the hypertensive cohort also exhibited a quadratic relationship between DBP and mean hippocampal volume; participants with readings at approximately 77 mmHg showing the largest volumes. Longitudinally, all groups experienced WML growth, despite different BP trajectories, further suggesting that WML expansion may occur despite or because of BP reduction in individuals with compromised vascular system. Conclusion: Overall, our study suggests that in the hypertensive group there is a valley of mid-range blood pressures displaying less pathology in the brain.